2017
DOI: 10.1016/j.exer.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of EGF receptor signaling on morphogenesis of eyelid and meibomian glands

Abstract: The epidermal growth factor receptor (EGFR) signaling has a pivotal role in the regulation of morphogenesis during development and maintenance of homeostasis in adult eyelid and its adnexa. Studies have demonstrated that during eyelid morphogenesis the EGFR signaling pathway is responsible for keratinocyte and mesenchymal cell proliferation and migration at the eyelid tip. For meibomian gland morphogenesis, EGFR signaling activation stimulates meibomian gland epithelial cell proliferation. EGFR signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The curved whiskers, wavy fur, and inflamed Meibomian glands in adult mice are consistent with a reduction in ADAM17/TGFα/EGFR signaling ( 45 , 60 , 61 ), which presumably also explains the inflammation of Zymbal glands. With respect to the curvy whiskers and wavy fur, the Adam17Δcyto mice resemble other mice with hypomorphic mutations in the ADAM17/EGFR pathways ( 16 , 44 , 45 ).…”
Section: Discussionmentioning
confidence: 54%
“…The curved whiskers, wavy fur, and inflamed Meibomian glands in adult mice are consistent with a reduction in ADAM17/TGFα/EGFR signaling ( 45 , 60 , 61 ), which presumably also explains the inflammation of Zymbal glands. With respect to the curvy whiskers and wavy fur, the Adam17Δcyto mice resemble other mice with hypomorphic mutations in the ADAM17/EGFR pathways ( 16 , 44 , 45 ).…”
Section: Discussionmentioning
confidence: 54%
“…EGF was considered associated with various ophthalmological diseases. 32–34 A previous study showed there is association between IL1A polymorphisms and primary open angle glaucoma. 35 CD40 and CD40LG were considered associated with pathogenesis of thyroid eye disease.…”
Section: Discussionmentioning
confidence: 98%
“…It is expressed in human meibomian gland epithelial cells as well, and its signaling increases the proliferation but not the differentiation [ 12 ]. EGFR activation promotes proliferation and inhibits differentiation of meibomian gland epithelial cells, and decreases processes related to fatty acid metabolism [ 13 ]. The HER2 receptor is the 2nd member of the EGFR family and can be involved in the regulation of epithelial cells; it may control cell growth, differentiation, or apoptosis (lateral signal transduction) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR activation promotes proliferation and inhibits differentiation of meibomian gland epithelial cells, and decreases processes related to fatty acid metabolism [ 13 ]. The HER2 receptor is the 2nd member of the EGFR family and can be involved in the regulation of epithelial cells; it may control cell growth, differentiation, or apoptosis (lateral signal transduction) [ 13 ]. HER2-inhibitors (HER, PER) get cells arrested in the G1 phase; therefore, survival and angiogenesis is suppressed.…”
Section: Discussionmentioning
confidence: 99%